2002
DOI: 10.1023/a:1025313214951
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Pituitary adenomas most commonly are identified as small, incidental microadenomas. They however may progress to macroadenoma forming intra and later suprasellar tumors which in about 1/3 of cases invade surrounding structures at the time of diagnosis. Mechanism of pituitary tumorigenesis remains still elusive. Because the value of karyotyping is limited by the technical problems related to cytogenetic methods, we studied the spectrum of chromosomal imbalances associated with pituitary adenoma using comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Classical cytogenetic studies have demonstrated differences in degree of chromosomal alterations among pituitary adenomas, but the results are inconsistent (55, 56). …”
Section: Discussionmentioning
confidence: 99%
“…Classical cytogenetic studies have demonstrated differences in degree of chromosomal alterations among pituitary adenomas, but the results are inconsistent (55, 56). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased expression of the pituitary tumor-transforming gene (PTTG), the index mammalian securin that enables faithful chromatid separation during mitosis (15)(16)(17), was also associated with aneuploidy in these adenomas (16). Loss of heterozygosity (18) and somatic copy number alterations (SCNAs) were reported in secreting and more aggressively growing sporadic pituitary adenomas (18)(19)(20)(21)(22). De novo SCNAs, commonly seen in tumors, may arise as a consequence of DNA damage and genome instability and can result in cell dysfunction (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Bates et al (88) studied loss of heterozygosity (LOH) associated with an aggressive behaviour and identified a significantly higher frequency of LOH in invasive tumours compared with non-invasive tumours and demonstrated that allelic deletion in the invasive tumours is clustered at four loci: 11q13 (multiple endocrine neoplasm type 1 (MEN1) and aryl hydrocarbon receptor-interacting protein (AIP)), 13q12-14, 10q26 and 1p. The frequency of these alterations has been confirmed in other publications (58,89,90,91,92,93,94). To identify the specific alterations associated with tumour behaviour and evaluate the impact of genomic alteration on transcriptomic activity, we recently conducted an integrated genomic profiling study of PRL tumours classified according to our pathological classification (58).…”
Section: Chromosomal Alteration By Comparative Genomic Hybridisation mentioning
confidence: 59%